2011
DOI: 10.1055/s-0030-1270836
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Neoadjuvant Chemotherapy on Pulmonary Structures: A Quantitative Analysis

Abstract: Neoadjuvant chemotherapy did not increase postoperative morbidity or mortality. The decreased tensile strength of pulmonary vessels and bronchi after neoadjuvant therapy should alert thoracic surgeons to possible surgical complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…By analyzing the surgical approach, we observed a high rate of thoracotomy in two treatment groups, and the rate in immunotherapy patients was higher than that in chemotherapy patients (75% vs. 62.5%, P = 0.496). According to recent studies, a low tensile strength of the pulmonary vessels and bronchi was found in patients receiving neoadjuvant chemotherapy ( 18 ), and more severe destruction of elastic fibers of the blood vessels, pulmonary interstitial exudation, vascular wall degeneration, fibrinoid necrosis, and fibrosis was found in patients receiving neoadjuvant immunotherapy ( 19 ). Such histological changes could explain the high rate of thoracotomy in two treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…By analyzing the surgical approach, we observed a high rate of thoracotomy in two treatment groups, and the rate in immunotherapy patients was higher than that in chemotherapy patients (75% vs. 62.5%, P = 0.496). According to recent studies, a low tensile strength of the pulmonary vessels and bronchi was found in patients receiving neoadjuvant chemotherapy ( 18 ), and more severe destruction of elastic fibers of the blood vessels, pulmonary interstitial exudation, vascular wall degeneration, fibrinoid necrosis, and fibrosis was found in patients receiving neoadjuvant immunotherapy ( 19 ). Such histological changes could explain the high rate of thoracotomy in two treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Kim [ 22 ] also reported a 20% 90-day mortality after right-sided pneumonectomy. On the other hand, there are also some recent studies published showing that this high-risk procedure can be performed with acceptable mortality rates from 3 to 10% [ 2 , 3 , 5 8 , 10 , 23 ]. More recently Kim et al .…”
Section: Discussionmentioning
confidence: 99%
“…Resulta muy difícil medir o cuantificar un parámetro como complejidad técnica, porque dependerá de muchos factores, especialmente de la experiencia o destreza del cirujano. Sin embargo, como ya proponían Ceylan y col. hace más de una década, parece importante intentar cuantificar de alguna manera las peculiaridades que detectamos en el campo quirúrgico e intentemos recogerlas utilizando un lenguaje común (34). Esto cobra especial importancia en una era en la que el tratamiento neoadyuvante parece que va a ser cada vez más frecuente en pacientes potencialmente quirúrgicos (35).…”
Section: D) Neumonectomíaunclassified